Determinants of physical activity among 6856 individuals with diabetes: a nationwide cross-sectional study. Issue 4 (17th August 2022) - Mortensen, Sofie Rath; Kristensen, Peter Lund; Grøntved, Anders; Ried-Larsen, Mathias; Lau, Cathrine; Skou, Søren T
Abstract : Introduction: The aims of this cross-sectional study were to (1) describe habitual physical activity and adherence to WHO recommendations, and (2) investigate the association of comorbidity, obesity, stress, and health-related quality of life (HRQoL) with moderate to vigorous physical activity (MVPA) among individuals with diabetes. Research design and methods: This study included 6856 participants with diabetes from the Danish National Health Survey from 2017. The primary outcome measure was weekly MVPA. Exposures included self-reported number of conditions, body mass index (BMI), perceived stress, and HRQoL. Mean difference in MVPA across exposures was estimated by multiple linear regression analyses. Results: Forty per cent of individuals with diabetes were not adherent to WHO recommendations for physical activity. Individuals with diabetes had higher BMI, more comorbidities, higher perceived stress, and lower HRQoL. Individuals with three or more comorbidities were significantly associated with lower weekly MVPA (−0.48 hours/week, 95% CI −0.88 to −0.07) compared with individuals with no comorbidity. Furthermore, overweight or obese (class I–III) individuals engaged in significantly less weekly MVPA (obese class III vs normal weight: −1.98 hours/week, 95% CI −2.49 to −1.47). Higher perceived stress was significantly associated with lower weekly MVPA (−1.76 hours/week, 95% CI −2.18 to −1.34) versus low perceived stress. Finally, having low physical and mental HRQoL was associated with lower weekly MVPA (−0.93 hours/week, 95% CI −1.19 to −0.66 and −0.39 hours/week, 95% CI −0.71 to −0.08 respectively vs moderate or high HRQoL). Conclusions: We found that 40% of individuals with diabetes do not engage regularly in adequate physical activity. Comorbidities, higher BMI, higher perceived stress, and lower HRQoL were associated with less engagement in physical activity. This study suggests that subgroups of individuals with diabetes are at higher risk of physical inactivity.